Influence of logistic factors in modern machine building enterprise - Rossynska, Lika (Management and Entrepreneurship: Trends of Development, 2017)
Purpose. An important condition to successfully enter the European market is the implementation and application of a management pattern based on a logistic approach.Design/methodology/approach. The basic principles of the research are systematic and comparative methods, structural-functional approaches have been used.Findings. To date, the logistics factors are the main driving factor for entering a competitive level. The important constituent of the static function of the contemporary machine-building enterprise is implementing of the concept of a logistical approach to its management, which is for majority of machine-building enterprises is a special condition for ensuring a rapid response to the demand of domestic and foreign customers. The analysis of output volume of machine-building products for 2014-2017 years allowed to establish that there is a slight growth in the industry. However, the presence of positive results of logistics activities is observed only at the enterprises where the management is trying to implement integration logistics with information management systems. An important condition to successfully enter the European market is the implementation and application of a management pattern based on a logistic approach.Consequently, the results of the research of machine-building enterprises testify to the fact that some of them are already trying to use the logistic principles of management of material flows of the enterprise. However, the presence of positive results of logistics activities is observed only in enterprises where the management is trying to implement integration logistics with information management systems. Determining the factors of logistics that contribute to the implementation of the logistics approach in the machine-building enterprise helps to identify the possibility of increasing the efficiency, productivity, reliability and flexibility of the machine-building enterprise.Research limitations / implications. The paper clearly provides direction to evaluate the influence of the logistic approach of industrial enterprises on their development.Originality/value. Such knowledge will help to increase the competitiveness of the Ukrainian machine building enterprise and accelerate the process of integrating the country into the world economy